Energy system contribution to Olympic distance in flat water kayaking (500 and 1000 m) in highly trained subjects. - Zouhal, H.; Le Douairon Lahaye, S.; Abderrahaman, A. B.; Minter, G.; Herbez, R.; Castagna, C. (The Journal of Strength and Conditioning Research, 2012)
Olympic flat water kayaking races take place over a distance of 500 and 1,000 m. This study was designed to determine the aerobic and anaerobic contributions to 500- and 1,000-m races during flat water paddling in open water, using the accumulated oxygen deficit (AOD) method. Seven internationally ranked athletes, specialized in 500-m races and familiar with 1,000-m races, participated in this study (age: 21.86 ± 1.68 years, body mass: 78.54 ± 3.41 kg, height: 1.84 ± 0.03 m, body fat%: 10.14 ± 0.69%). All the participants performed 3 track-kayaking sessions. During the first session, the maximal oxygen uptake and maximal aerobic speed were determined using a portable gas analyzer and a global positioning system. During the successive testing sessions, paddlers performed in a randomized counterbalanced order a 500- and a 1,000-m race under field conditions (open water track kayaking). The 500-m AOD was significantly higher than the 1,000-m AOD (18.16 ± 4.88 vs. 9.34 ± 1.38 ml/kg, p < 0.05). The aerobic contribution resulted in being higher during the 1,000 m compared with that in the 500-m condition (86.61 ± 1.86% vs. 78.30 ± 1.85%, respectively, p < 0.05). The results of this study showed that the 500- and 1,000-m races are 2 physiologically different kayaking events with a higher aerobic contribution in the 1,000 m. The training prescription for elite athletes should emphasize aerobic high-intensity training for the 1,000 m and anaerobic short-term training for the 500-m race.